2018
DOI: 10.1080/20009666.2018.1514933
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid induced acute liver injury resulting in hepatic encephalopathy- a case report and literature review

Abstract: Valproic acid (VPA) is a commonly used agent in the management of seizures and psychiatric disorders. Hyperammonemia is a common complication of VPA with 27.8% of patients having elevated levels – that is unrelated to hepatotoxicity and normal transaminases. Common side effects include obesity, insulin resistance, metabolic disorder and severe forms of hepatotoxicity. Other rare and idiosyncratic reactions have been reported, one of which is presented in our case. A 27-year old patient presented with hyperammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
0
15
0
4
Order By: Relevance
“…Our data showed that GABA transaminase is not only highly enriched in brain but also in the liver with the highest abundance level. The unknown liver toxicity could be caused by the inhibition of GABA transaminase in liver (47).…”
Section: Proteome Genetic Diseases and Drug Targetsmentioning
confidence: 99%
“…Our data showed that GABA transaminase is not only highly enriched in brain but also in the liver with the highest abundance level. The unknown liver toxicity could be caused by the inhibition of GABA transaminase in liver (47).…”
Section: Proteome Genetic Diseases and Drug Targetsmentioning
confidence: 99%
“…The toxicity of valproic acid is closely linked to impaired liver function but remains complex [ 26 , 27 ]. Fan and colleagues reported on a small sample of COVID-19 patients who one-third of patients presented abnormal liver function [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Valproate is commonly used in the management of epileptic seizures. 13 Documented side effects of valproate include obesity, insulin resistance, metabolic disorder, and severe forms of hepatotoxicity. Elevated transaminase levels have been reported in up to 5% to 10% of patients taking valproate.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated transaminase levels have been reported in up to 5% to 10% of patients taking valproate. 13,14 There is a need to routinely monitor liver function and full blood count in patients receiving AED therapy. This study set out to determine the pattern of utilization of AEDs, extent of documentation of adverse drug reactions associated with AEDs, the extent of monitoring of the hematologic effects of carbamazepine, as well as the extent of monitoring of the hepatic effects of valproate in patients with epilepsy receiving treatment with these agents in 2 selected neurologic clinics in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation